Radiation damage in the LHCb vertex locator - Affolder, A; Akiba, K; Alexander, M; Ali, S; Artuso, M; Benton, J; van Beuzekom, M; Bjornstad, P; Bogdanova, G; Borghi, S; Bowcock, T; Brown, H; et al. (2013)
The LHCb Vertex Locator (VELO) is a silicon strip detector designed to reconstruct charged particle trajectories and vertices produced at the LHCb interaction region. During the first two years of data collection, the 84 VELO sensors have been exposed to a range of fluences up to a maximum value of approximately 45 × 1012 1 MeV neutron equivalent (1 MeV n eq). At the operational sensor temperature of approximately -7 °C, the average rate of sensor current increase is 18 μA per fb -1, in excellent agreement with predictions. The silicon effective bandgap has been determined using current versus temperature scan data after irradiation, with an average value of Eg = 1.16±0.03±0. 04 eV obtained. The first observation of n+-on-n sensor type inversion at the LHC has been made, occurring at a fluence of around 15 × 1012 of 1 MeV neq. The only n+-on-p sensors in use at the LHC have also been studied. With an initial fluence of approximately 3 × 1012 1 MeV neq, a decrease in the Effective Depletion Voltage (EDV) of around 25 V is observed. Following this initial decrease, the EDV increases at a comparable rate to the type inverted n +-on-n type sensors, with rates of (1.43±0.16) × 10 -12 V/ 1 MeV neq and (1.35±0.25) × 10 -12 V/ 1 MeV neq measured for n+-on-p and n+-on-n type sensors, respectively. A reduction in the charge collection efficiency due to an unexpected effect involving the second metal layer readout lines is observed.© CERN 2013.